Kindler syndrome with palmoplantar hyperhidrosis and blonde hair - Anshul Maheshwari; Daulat Ram Dhaked; Deepak K Mathur; Puneet Bhargava (Wolters Kluwer Medknow Publications, 2015)
Kindler syndrome (KS) is a very rare genodermatosis characterized by acral blistering starting in infancy along with photosensitivity, progressive poikiloderma, cutaneous atrophy, and a variable degree of mucosal involvement. A large number of other cutaneous and extracutaneous features have been described, which aid in diagnosing it. Generally KS has been found to be associated with hypohidrosis/anhidrosis. We herein present a rare case of KS with unique features.